Natural Potential for Exploiting Solar Radiation Energy in Salah al-Din Governorate - Ibraheem, Rafea K. (Journal of Tikrit University for Humanities, 2024)
Energy is the main pillar of economic development, and its production and consumption are among the main indicators to describe the strength and economy of the country, as the indicator of per capita energy consumption in the country has become evidence of the extent of its progress and advancement among the countries of the world. The study aims to know the geographical potential, represented by the geographic location and climatic factors of Salah al-Din Governorate, and its role in the possibility of exploiting solar radiation energy and generating clean electrical energy that fills the shortfall in equipping the national system and investing it in various economic sectors to achieve sustainable development goals..